Synthesis and Characterization of Hydroxyapatite-Nanosilver as Anti Bacteria that Cause Dental Caries - Lestari, Nanda Revita Dwi; Cahyaningrum, Sari Edi (Indonesian Journal of Chemical Science, 2022)
The formation of dental caries is the result of the activity of Streptococcus mutans bacteria. Various attempts have been done to prevent dental caries. One of them is using oral preparations containing antibacterial compounds Hydroxyapatite-NanoSilver which is an active ingredient that can provide antimicrobial effects to prevent dental caries. This study aims to synthesize and characterize nanosilver hydroxyapatite as an antibacterial that causes dental caries. Physicochemical characterization and antibacterial test towards Streptococcus mutans bacteria with the active ingredient hydroxyapatite-nanosilver. In this study, hydroxyapatite-nanosilver materials with variations in nanosilver concentration of 4 ppm were used; 7 ppm; 10 ppm; 13 ppm; and 15 ppm. The results of FT-IR characterization showed the functional groups O-H, C=O, CO32-, and PO43-. The results of the PSA test showed that the hydroxyapatite-nanosilver formulation with a concentration of 10 ppm had the smallest nanoparticle size of 80.89 nm. Measurement of antibacterial activity test showed that the hydroxyapatite-nanosilver formulation was able to inhibit the growth of Streptococcus mutans bacteria. The highest diameter of resistance to the growth of mutant Streptococcus bacteria in hydroxyapatite-nanosilver formulations is 22.5 mm at a nanosilver concentration of 4 ppm.